ANALISIS KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK PADA MATERI ALJABAR KELAS VII SMP - Op.sunggu, Katarina Natalia; Ayal, Carolina S; Huwaa, Novalin C (Jurnal Pendidikan Matematika Unpatti, 2023)
Reasoning ability is the ability to think logically to draw a conclusion based on the previous statement. Mathematical reasoning ability can be seen from the test results of students in working on questions made based on indicators of mathematical reasoning ability. This study aims to describe students' mathematical reasoning abilities in algebraic material. The type of research used was qualitative research with 3 students selected from 24 class VII students of Ambon Catholic Junior High School based on the results of mathematical reasoning ability tests on algebraic material with high, medium and low mathematical reasoning ability categories. The results showed that subjects with high mathematical reasoning abilities can fulfill each indicator of mathematical reasoning ability. Student with moderate category fulfilled 3 indicators of mathematical reasoning. Student with low mathematical reasoning abilities did not meet all the indicators